Kajian kesesuaian lingkungan untuk pengembangan wisata di Pantai Ganting, Pulau Simeulue, Provinsi Aceh - Herdiana Mutmainah; Gunardi Kusumah; Try Altanto; Koko Ondara (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2016)
Abstract. Simeulue Island is situated Indian Ocean in western part of Aceh Province, this is one of the outer island in Indonesia. Simeulue has big potency in marine resources such as clean waters and beautiful beach, coral reefs and mangrove ecosystems. Therefore, Simeulue is very promising as an ecotourism destination. The objective of present study was to evaluate the condition of the water quality and the potency for a marine ecotourism development. The feasibility study was conducted on August in Ganting Beach, Village of Kuala Makmur, Simeulue Island. The purposive random sampling method was used to determine twelve sampling stations. The measured water quality parameters were pH, temperature, salinity, turbidity, dissolved oxygen, brightness, BOD5, odors, oil and debris. These parameters were analyized and mapped using software ODV, and then compared to the sea water quality standard for marine tourism as well as the characteristics of the coast to the suitability index of recreational area. The results showed that the water quality of Ganting Beach is very suitable for recreational activities (index 77, category S1) andit is suitable for swimming and also for boating tourism activities, banana boats and jet skis (index 16, category S2).Keywords: water quality; marine tourism; Ganting Beach Abstrak. Pulau Simeulue, merupakan salah satu pulau terdepan sebelah barat Negara Kesatuan Republik Indonesia (NKRI), dan terletak di Samudera Hindia.Simeulue memiliki potensi sumberdaya laut yang besar, diantaranya perairan yang besih dan jenih, pantai yang indah, terumbu karang dan hutan bakau, sehingga sangat berpotensi untuk dikembang menjadi tujuan wisata. Penelitian ini bertujuan untuk menilai kondisi kualitas perairan dan potensi kesesuaian wisata Pulau Simeulue.Penelitian ini dilaksanakan pada bulan Agustus 2015 bertempat di Pantai Ganting, Kelurahan Kuala Makmur, Kabupaten Simeulue. Sebanyak 12 lokasi pengambilan sampel kualitas air ditetapkan secara purposive random sampling. Kualitas air yang diukur meliputi; pH, suhu, salinitas, kekeruhan, oksigen terlarut, kecerahan, BOD5, bau, lapisan minyak dan sampah. Data tersebut kemudian dipetakan dan dianalisis menggunakan software Ocean Data View (ODV), kemudian dibandingkan dengan baku mutu air laut untuk wisata bahari serta karakteristik pantai untuk indeks kesesuaian kawasan wisata rekreasi. Hasil penelitian menunjukkan bahwa kualitas perairan Pantai Ganting sangat sesuai untuk kegiatan rekreasi dan berenang (indeks 77, kategori S1) dan sesuai untuk kegiatan wisata berperahu, banana boat dan jet ski (indeks 16, kategori S2).Kata kunci:kualitas perairan; wisata bahari; Pantai Ganting.